System Election Decision Support Member the Best Women Farmers Group in Bumi Arum Village Using the Simple Additive Weighting Method - Nurul Fauci, Rinawati, Mega (YHMM PUBLISHING, 2023)
Group (KWT) is a receptacle for accommodate a number of Woman For to form a same plan and goal. Bumiarum Village has a KWT consisting of from women farmers who play a role active in matter help field agriculture. Application This made with SAW (Simple Additive Weighting) method of searching summation weighted from the performance rating on each alternative to all attributes. The SAW method can help in taking decision a case, will but calculation with use This SAW method only those that produce mark the biggest one that will be selected as the best alternative. Calculation will in accordance with method This if selected alternative​ fulfil criteria that have been determined. With Use system Supporter decision election member group woman farmer best in the village arum earth uses method Simple Additive Weigtihng (SAW). helping Bumiarum Village For know ranking KWT members from results weight criteria that have been determined, so give information addition moment will determine A options. System Supporter decision This made website based with Language PHP programming and MSQL database for data storage.